Implementasi Literasi Digital Dalam pembelajaran Pendidikan Agama Islam Di Madrasah - Sholikhah, Zaimatus; Rizka Putri As-syafi’I; Sutiah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
In the current digital era, the use of social media as online media is increasingly growing. The millennial generation is the largest user in the world of social media today. In implementing digital literacy, schools must monitor their students' access to social media. So teachers must really be able to monitor and sort out digital literacy that is suitable for their students. The application of digital media in Islamic Religious Education Learning in madrasas presents both opportunities and challenges. The focus of this research includes planning, implementation and evaluation of digital literacy in Islamic religious education. The method used in this research is qualitative which involves the presence of researchers, interviews and documentation. The research results show (1) planning, holding learning tool workshops in accordance with the curriculum currently used, preparing materials and methods that will be used in learning. (2) in its implementation, implementing several applications to support the continuity of the learning process, such as: YouTube, school website, power point, classroom, and the Filmora video editing application. (3) Evaluate the implementation of digital literacy using applications specifically designed by schools and Web tools, such as: E-exam, Socrative.com, and Quizizz